3D-printed metal electrodes for electrochemical detection of phenols. (December 2017) - Cheng, Tay Siew; Nasir, Muhammad Zafir Mohamad; Ambrosi, Adriano; Pumera, Martin
Graphical abstract: Highlights: Metal 3D printing is used to produce helical-shaped electrodes for electrochemical applications. 3D printed stainless steel electrode coated with a gold film is used for phenols detection. Additive manufacturing allows for rapid prototyping of complex shapes. Gold plated 3D-printed electrode produces superior performances than conventional carbon based electrodes. Abstract: 3D printed metal electrode modified by means of electroplating methodologies was tested and compared with conventional glassy carbon (GC) electrode for the individual and simultaneous electrochemical detection of phenol and p -aminophenol ( p -AP) in aqueous solution via cyclic and differential pulse voltammetry. The 3D printed gold-plated electrode produced two distinct oxidation peaks for phenol and p -AP at lower anodic potentials as compared to GC electrode. It also showed improved analytical performance with higher sensitivity for p -AP detection. The fabricated electrode was stable at anodic potentials and the inherent electrochemistry of the electrode did not interfere with the electrochemical signals obtained. Thus, we have demonstrated a potential application of 3D printing technology for detection of phenolic compounds in environmental samples.